2007
DOI: 10.1111/j.1365-2257.2006.00879.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial remission of a newly diagnosed diffuse large B‐cell non‐Hodgkin's lymphoma in a hemodialysis patient after administration of immuno‐chemotherapy with rituximab‐CHOP

Abstract: Summary To date little data exist about treatment of hematologic malignancies in patients with end‐stage renal disease (ESRD). While administration of immunochemotherapy comprising the CD20‐antibody rituximab is a well‐established treatment strategy in patients with normal renal function, little information on safety and efficacy is available in the setting of ESRD. Here we describe for the first time a hemodialysis patient suffering from diffuse large B‐cell Non‐Hodgkin's lymphoma (DLBCL) who was treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…Most of the available studies regarding the use of doxorubicin in patients on HD have been conducted in haematological disorders. 34 In this setting, the drug is administered at standard doses without toxicity. Doxorubicin and its major metabolite, doxorubicinol, are poorly metabolised by the kidney, although it has been shown that the two compounds exhibit an increased AUC in patients with renal insufficiency.…”
Section: Anthracyclinesmentioning
confidence: 99%
“…Most of the available studies regarding the use of doxorubicin in patients on HD have been conducted in haematological disorders. 34 In this setting, the drug is administered at standard doses without toxicity. Doxorubicin and its major metabolite, doxorubicinol, are poorly metabolised by the kidney, although it has been shown that the two compounds exhibit an increased AUC in patients with renal insufficiency.…”
Section: Anthracyclinesmentioning
confidence: 99%
“…The anthracycline DXR and its major metabolite doxorubicinol are not predominantly eliminated by the kidneys, but the AUCs of DXR and doxorubicinol have been found to be higher in HD patients compared to non‐HD patients 62 . Some investigators have recommended a 10%‐20% dose reduction of DXR and VCR in HD patients, 27 while most others have recommended the standard dose 3,25 . Data concerning removal of DXR and VCR by HD are limited, and therefore these drugs should be administered after HD 3,4 .…”
Section: Individual Treatment Methodsmentioning
confidence: 99%
“…Une étude de pharmacocinétique du rituximab réalisée chez un patient hémodialysé rapporte que les taux plasmatiques sont comparables à ceux des patients ayant une fonction rénale normale après administration de 375 mg/m 2 par semaine pour le traitement d'un lymphome B [8]. Dans le cas d'un patient atteint d'un lymphome B traité par le protocole R-CHOP avec du rituximab administré à 375 mg/m 2 tous les 21 jours, les auteurs rapportent une bonne tolérance ainsi qu'une bonne efficacité du traitement [9]. Par ailleurs, il existe plusieurs études, hors cancérologie, rapportant également une bonne efficacité et une bonne tolérance du rituximab administré à des posologies allant de 50 à 375 mg/m 2 chez des patients hémodialysés [10,11].…”
Section: Rituximabunclassified